1993
DOI: 10.1530/jrf.0.0980467
|View full text |Cite
|
Sign up to set email alerts
|

Biopsy and sex determination by PCR of IVF bovine embryos

Abstract: Sex of early bovine embryos was determined by polymerase chain reaction (PCR) using a single blastomere removed at the 16-32 cell stage. Embryos were produced in vitro and biopsied on the fifth day after in vitro fertilization. Biopsied embryos were cultured on a cumulus cell monolayer until embryo transfer. For the PCR, one pair of bovine-specific and one pair of Y-chromosome-specific primers were used. Definite signals following PCR amplification were obtained in 95.4% of cases indicating that one blastomere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
31
0
1

Year Published

1995
1995
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(35 citation statements)
references
References 15 publications
3
31
0
1
Order By: Relevance
“…Cell sampling by biopsy has been applied to IVP bovine embryos at the 16-to 32-cell stage [47,48], morula-stage [49,50], and blastocyst-stage [51,52]. Since efficiency of sexing decreased significantly when less than five cells were subjected to PCR [52], the larger sampling size (8-10 cells) has been recommended for successful sexing of the embryos [53].…”
Section: Cryopreservation Of Sex-identified Embryosmentioning
confidence: 99%
“…Cell sampling by biopsy has been applied to IVP bovine embryos at the 16-to 32-cell stage [47,48], morula-stage [49,50], and blastocyst-stage [51,52]. Since efficiency of sexing decreased significantly when less than five cells were subjected to PCR [52], the larger sampling size (8-10 cells) has been recommended for successful sexing of the embryos [53].…”
Section: Cryopreservation Of Sex-identified Embryosmentioning
confidence: 99%
“…When embryo sexing is performed with male-specific target sequences, one cannot distinguish the false-negative amplification caused by sampling errors or from lack of amplification in female samples. To solve this problem, various combination of two different PCR primer sets, one for a male-specific sequence and another for a sequence common to both sexes, have been examined as a multiplex PCR to obtain internal bovine control for embryo sexing [12][13][14][15][16][17].…”
mentioning
confidence: 99%
“…Takeuchi et al [17] reported that they collected human single blastomeres at the 4-and 8-cell stages by the enucleation, aspiration, or extrusion method, and the viability of embryos at the 4-cell stage was not affected by the aspiration or extrusion method, and the viability of embryos at the 8-cell stage was not affected by either method. In cattle, single blastomeres at the 16-to 32-cell stages collected by the aspiration method were transplanted, and fertility similar to that of the control subjects was obtained [6]. In this study, the 7/8 embryos obtained by the extrusion method developed to blastocysts without difference from the development of intact embryos at the 8-cell stage, showing that the collection of embryos by the extrusion method causes less inhibition of embryonic development.…”
Section: Discussionmentioning
confidence: 54%
“…They reported that PCR product common to both sexes was detected in 95% of the samples, and the sex ratio (male ratio) was 65.8%. Macháty et al [6] collected single blastomeres from embryos at the 16-and 32-cell stages, and determined the sex with male-specific and gender neutral primers. The detection rate for PCR product common to both sexes was 95%, but the sex ratio was not mentioned.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation